Thermal annealing induced mazy structure on MoO3 thin films and their high sensing performance to NO gas at room temperature. Issue 16 (December 2016) - Li, Y.X.; Song, Z.X.; Jiang, F.; Sun, Q.; Ma, F.; Wang, H.R.; Chen, K.
Abstract: MoS2 thin films were prepared by radio frequency (RF) magnetron sputtering and then annealed in air. X-ray diffraction (XRD), field-emission electron scanning microscopy (FESEM) and transmission electron microscopy (TEM) were adopted to characterize the phase structure and surface morphology. Interestingly, upon thermal annealing in air, MoS2 thin films changed into α-MoO3 with mazy morphology, and the thin films were covered by MoO3 nano-sheets with a length of 30–50 nm and a width of 10 nm. α-MoO3 thin films with mazy morphology showed excellent response to NO gas at room temperature. The response of 5% and 92% was obtained at 5 ppm and 200 ppm, respectively, and the response and recovery times were 30 s and 1500 s. Moreover, the mazy structure of MoO3 exhibited good selectivity to NO gas with respect to SO2, NH3 and H2 gases. The high surface-to-volume ratio was the dominant factor for high sensing performance.